Teaching and learning challenges faced by teachers and young learners in early literacy: Reading and writing in EFL context - Anisa Kurniadhani Suryo Putri (Universitas Merdeka Malang, 2024)
This article aimed at identifying and investigating the teaching and learning strategies in early literacy which were used by the English teaching, obstacles faced by learners, and the solution in the teaching reading and writing for young learners especially in foreign language context. It was collected through peer review journals, theories, articles, books and finding from previous studies. Based on the researches and studies made on L1 and L2 acquisition, the learners who completed their first language acquisition have been found more successful in L2 and FL acquisition. The results of this article show that the teachers can integrate L1, L2 or Foreign Language in teaching reading, and also appropriate materials. Therefore, some strategies for early literacy for EFL learners are provided; teaching phonological awareness and making balancing between bottom-up and top-down processing skills.